2016
DOI: 10.1016/j.jpowsour.2016.06.046
|View full text |Cite
|
Sign up to set email alerts
|

Accessible triple-phase boundary length: A performance metric to account for transport pathways in heterogeneous electrochemical materials

Abstract: The performance of materials for electrochemical energy conversion and storage depends upon the number of electrocatalytic sites available for reaction and their accessibility by the transport of reactants and products. For solid oxide fuel/electrolysis cell materials, standard 3-D measurements such as connected triple-phase boundary (TPB) length and effective transport properties partially inform on how local geometry and network topology causes variability in TPB accessibility. A new measurement, the accessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…This requires not only good interconnection from the current collector to the separator but also good interconnection in between the reaction areas, that is, RNs. A similar result has been obtained by Nakajo et al 43 They studied electrochemical materials and showed that the connection of the triple phase boundary is important to obtain good performances.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…This requires not only good interconnection from the current collector to the separator but also good interconnection in between the reaction areas, that is, RNs. A similar result has been obtained by Nakajo et al 43 They studied electrochemical materials and showed that the connection of the triple phase boundary is important to obtain good performances.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…The 3D segmentation was performed using the same Matlab routines with calls to Avizo for marker generation based on the variance of the grayscale distribution, image gradient, and watershed transform computations as described in Refs. [24,25]. Such method cannot guarantee the accurate treatment of all the localized detachments between Ni and YSZ.…”
Section: Methodsmentioning
confidence: 99%
“…The segmentation, which consists in assigning to each voxel belonging to a same material phase the same label, was based on the grayscale electron images using Matlab routines with calls to Avizo for image gradient and watershed transform computations. Further descriptions of the methods used for image processing and quantitative 3-D analyses are provided in (9). Figure 1a and 2b show overall and close-up 3-D views of the aligned grayscale and segmented datasets.…”
Section: Methodsmentioning
confidence: 99%